Quality of reporting of robot-assisted cholecystectomy in relation to the IDEAL recommendations: systematic review. Issue 5 (25th October 2022) - Kirkham, Emily N; Jones, Conor S; Higginbotham, George; Biggs, Sarah; Dewi, Ffion; Dixon, Lauren; Huttman, Marc; Main, Barry G; Ramirez, Jozel; Robertson, Harry; Scroggie, Darren L; Zucker, Benjamin; et al.
Abstract: Introduction: Robotic cholecystectomy (RC) is a recent innovation in minimally invasive gallbladder surgery. The IDEAL (idea, development, exploration, assessment, long-term study) framework aims to provide a safe method for evaluating innovative procedures. This study aimed to understand how RC was introduced, in accordance with IDEAL guidelines. Methods: Systematic searches were used to identify studies reporting RC. Eligible studies were classified according to IDEAL stage and data were collected on general study characteristics, patient selection, governance procedures, surgeon/centre expertise, and outcome reporting. Results: Of 1425 abstracts screened, 90 studies were included (5 case reports, 38 case series, 44 non-randomized comparative studies, and 3 randomized clinical trials). Sixty-four were single-centre and 15 were prospective. No authors described their work in the context of IDEAL. One study was classified as IDEAL stage 1, 43 as IDEAL 2a, 43 as IDEAL 2b, and three as IDEAL 3. Sixty-four and 51 provided inclusion and exclusion criteria respectively. Ethical approval was reported in 51 and conflicts of interest in 34. Only 21 reported provision of training for surgeons in RC. A total of 864 outcomes were reported; 198 were used in only one study. Only 30 reported a follow-up interval which, in 13, was 1 month or less. Conclusion: The IDEAL framework was not followed during the adoption of RC. Few studies were conducted within a research setting, many were retrospective, and outcomes were heterogeneous. There is a need to implement appropriate tools to facilitate the incremental evaluation and reporting of surgical innovation. Abstract : Robotic cholecystectomy (RC) is a recent innovation in minimally invasive gallbladder surgery. Disparity between adoption of new techniques and robust evaluation has been observed in other areas of surgery and we sought to evaluate whether IDEAL guidelines were followed in the context of RC. We found that the IDEAL framework was not followed, few studies were conducted within a research setting, many were retrospective, and outcomes were heterogeneous. This lack of incremental evidence impairs surgeons' ability to draw meaningful conclusions, undermining shared decision-making with patients. There is a need to implement appropriate tools to facilitate the incremental evaluation and reporting of surgical innovation